PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR FISIKA - E. Ewisahrani; Eva Nursa’ban; F Fathurrahmaniah (GRAVITY EDU : Jurnal Pembelajaran dan Pengajaran Fisika, 2021)
Research has been carried out entitled the application of the Make A Match cooperative learning model to increase the activity and learning achievement of physics class VII students of SMPN 2 Wera. This research is classroom action research (PTK) which consists of 2 cycles. The purpose of this study was to increase the activity and learning achievement of class VII students of SMPN 2 Wera. The results of this study were analyzed with qualitative data while the average value of student learning activities in the first cycle was 12.32 in the fairly active category and the average value in the second cycle was 14.29 in the active category, which means that there was an increase in learning activities. students from cycle I to cycle II, as well as analyzing with quantitative data which resulted in the average value of student achievement in cycle I was 66.32 with 73.52% classical completeness and in cycle II the class average score increased to 72, 21 with classical completeness of 94.12%, which means that classical completeness has been achieved and student learning achievement has increased. From the results of the study, it can be concluded that using the Make A Match cooperative learning model can increase the activity and learning achievement of class VII students of SMPN 2 Wera.